Pengelolaan Pengembangan Program Kecerdasan Kinestetik Anak Usia Dini Melalui Permainan Outbound - Irma Muti; Abdul Basir; Mariana Panji Ramadan (Jurnal El-Audi, 2021)
Learning in early childhood education is carried out with the concept of playing while learning. Learning is packaged in such a way that it can provide an atmosphere of active, innovative, creative, effective, fun, happy and meaningful learning. In this case the teacher designs learning with the aim of providing stimulation and helping develop potential as optimally as possible. Because at this age according to experts call it the golden age (golden age). This research is generally aimed at planning, implementing, evaluating the level of success, and supporting inhibiting factors in managing the development of kinesthetic intelligence programs through outbound games at PAUD Fathurrohim Balekambang Nagrak, Sukabumi Regency. The method used in this study is a non-experimental method with a case study approach that aims to obtain an overview of the development of kinesthetic intelligence for early childhood through outbound games with the research location at PAUD Fathurrohim Balekambang Nagrak, Sukabumi Regency. The findings from this study are that the planning of developing a kinesthetic intelligence program through outbound games includes learning objectives, learning materials, learning processes, and learning evaluations that are very different from learning activities in PAUD. In addition, there is a characteristic of learning activities at Fathurrohim Early Childhood which is found in the learning objectives which focus more on the aspects of physical motor development and development of moral behavior and life skills. Implementation of the development of kinesthetic intelligence programs through outbound games in addition to understanding the concept of early childhood also understands learning activities through outbound games.